Increased tax rates in the taxation system of the Republic of Lithuania - Bronius Sudavicius; Martynas Endrijaitis (Правоприменение)
The subject. The research covers analysis of legal regulation that sets the increased tax rate instrument and the comparison of this instrument with other similar legal instruments.The purpose of the article is to clarify the content of the increased tax rate as legal instrument of taxation, its place in the general tax system, as well as the assumptions and objectives of the application thereof. The authors dare to confirm or disprove hypothesis that increased tax rates can be considered as specific punitive measure applied to taxpayers.The methodology of the research includes the analysis of Constitution and legislation of Republic of Lithuania, system analysis, logical-analytical method, formal-legal interpretation of Lithuanian laws.The main results, scope of application. An increase in the tax rate means exceptional taxation conditions opposite to the application of tax reliefs. It should be noted that if the application of the tax reliefs is foreseen in practically all taxes applied in Lithuania, the increase of the tax rate is intended only in a few cases. Taxation system of Lithuania sets the possibility to apply increased tax rates for real estate, land, natural resources and environmental protection taxes if the respective conditions foreseen in legislation are met. This legal regulation forms the distinct legal instrument – the increased tax rate. The increased tax rates is the economic sanction that comes to effect for harmful or illegal behaviour. The consequences of these economic sanctions are very severe what makes this instrument being equal to legal responsibility. Furthermore, this research examines if the higher tax rate might be applied along with other forms of legal responsibilities, for example, fine under the tax law. When trying to answer the question whether it is correct to recognize the application of a higher tax rate as a legal liability measure, it is necessary to clarify the purposes of its application, the bases (assumptions) that differ in individual taxes. The legal presumption of the application of the calculation of real estate and land taxes at the increased rate is the compliance of the object of taxation with certain objective properties established by the legal acts, i.e. abandonment, non-use of the property or the use not for the intended purpose, which results in the inclusion of such property in special lists of objects subject to levy of increased tax rate. The increased tax rate on state-owned natural resources is applied when the extracted resources are undeclared, the declared quantity of extracted resources is lower than the quantity actually extracted or extraction of natural resources is performed without the permit. Therefore, the application of a higher tax rate on state natural resources or environmental pollution tax is a consequence of the improper performance of their obligations under the relevant tax laws, for the purpose of punishing for the breaches of tax laws. Meanwhile, none of the laws enshrining the imposition of an increased tax rate provides for any grounds for exempting the taxpayer from paying the increased tax rate.Conclusions. The higher tax rate is to be considered a specific punitive measure applied to taxpayers. This is confirmed by the logical analysis of the texts of tax laws. The application of the higher tax rate in all cases is determined by violations of legal acts (taxes or other) which allow this phenomenon to be seen as a specific form (instrument) of legal coercion (liability).